The interaction of MD-2 with small molecules in huanglian jiedu decoction play a critical role in the treatment of sepsis - Chen, Guirong; Wang, Xiaobo; Liu, Chang; Zhang, Mingbo; Han, Xueying; Xu, Yubin (Frontiers in Pharmacology, 2022)
Huanglian Jiedu Decoction (HJD) is used for treating sepsis in China, while the mechanism of the active components from HJD and active components formulation (ACF) on anti-sepsis were not clear. Molecular docking, surface plasmon resonance (SPR), ELISA, Real-time PCR and western blot were used to assay the possible mechanism in vitro. The efficacy and mechanism of active ACF and HJD were assessed by pharmacodynamics and metabolomics analysis. The results showed that palmatine, berberine, baicalin and geniposide show good binding capacity to MD-2; can decrease the release of NO, TNF-α, IL-6, and IL-1β; inhibit the mRNA expression of iNOS, TNF-α, IL-6, IL-1β, and COX-2; and down-regulate the protein expression of MD-2, MyD88, p-p65, and iNOS induced by LPS; which indicated that they can inactivated the LPS-TLR4/MD-2-NF-κB pathway. Thus, the ACF were formed and the pharmacodynamics assay suggested that ACF can reduce inflammatory cell infiltration and organs damage in accordance with HJD. Furthermore, 39 metabolites were selected and identified, which revealed that most the molecular mechanism on anti-sepsis of ACF and HJD were consistent, but ACF might alleviate physical damage caused by HJD through regulating metabolites such as 3-hydroxyanthranilic acid. ACF could represent HJD as a new formulation to treat sepsis.